Teori Pembuktian Sederhana Dalam Perkara Kepailitan Dan Penundaan Kewajiban Pembayaran Utang - Harding, Haryadi (Pamulang Law Review, 2024)
In cases of bankruptcy and postponement of debt payment obligations (PKPU), cases are often filed repeatedly because the provisions of Article 1917 of the Civil Code or the principle of nebis in idem have been excluded in Law Number 37 of 2004 and in cases of bankruptcy and postponement of debt payment obligations adheres to a simple proof system, namely the fact of two or more creditors and the fact that the debt is overdue and unpaid. Therefore, the method of approach used in this research will refer to the approach to regulations and to cases that are filed repeatedly with the data processing process using qualitative data processing methods to process data that is narrative or text with a deductive model, namely combining theories related to the subject matter of this research and looking at the facts that occur in the world of law enforcement, especially in cases of Bankruptcy and Postponement of Debt Payment Obligations, so that a result can be obtained regarding the effectiveness of the application of simple proof in ensuring the upholding of the principle of legal certainty.